The economics of development and planning - Jhingan, M. L. (New Delhi : Konark, 1995)
The book examines the problems of economic development of underdeveloped countries. This edition has been revised and enlarged. A new chapter on 'Harris-Todaro Model of migration and Unemployment has been added. Chapters 69, 71, 73 and 78 in part seven have been rewritten. To update data relating to planning in India after the seventh plan, some macroeconomic indicators of the Indian economy have been given at the end of the book.
Includes bibliographical references: p. 853-856.
oif 15/07/2014
Loans
Keywords: Economic development; Economic policy; Developing countries; India